Table of Content - - (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content: 1. Terrorism Crimes and Financing in Saudi law and international agreements Dr. Amira Mohamed Ibrahim Satti 2. The counter administrative decision and its applications in the Board of Grievances in the Kingdom of Saudi Arabia. Abdul Majeed Abdullah Khalifa Al-Thaqafi 3. The impact of spoken speech on customer trust: An applied study in the Saudi Arabian Airlines Company during the year 1444 AH Mohamed Saad Maeed Al Zuhair Al-Shahrani 4. The Impact of Knowledge Management on Institutional Performance: An Applied Study on Greater Amman Municipality Dr. Amer Zaal Al-Jaafreh 5. The role of entrepreneurial leadership in achieving institutional excellence: A field study on the employees of the University of Tabuk (2022-1444) Setah Mofareh Al-Roqi, Dr. Walaa Abdullah Abdul Rahman Al-Mustadi 6. An Investigation into How Fluctuations in Global Crude Oil Prices Impact Tadawul All-Shares Index (January 1995-December 2017) Alyaa Talal Al-Ghanmi